Strategi Pelestarian Prasasti Bukit Siguntang dalam Meningkatkan Daya Tarik Wisata Sejarah Kerajaan Sriwijaya - Jarevsi, Jarevsi; Yusuf, Hudaidah (Jurnal Artefak, 2025)
The research analyses the preservation strategy of Bukit Siguntang inscription as an effort to increase public awareness of cultural heritage and increase historical tourism attraction. Using a qualitative approach, the research aims to understand and analyse the various approaches applied in preserving the inscription, challenges and opportunities, as well as its impact on tourism. The results showed that communication strategies, participatory models, utilisation of digital technology, curative and preventive approaches as effective efforts in cultural heritage preservation that can increase public awareness of cultural heritage and attract more visitors. In addition, SWOT analysis is used in identifying factors that affect preservation. Through this holistic and collaborative approach, the Bukit Siguntang inscription is preserved, making it an educational tool to enrich historical-cultural understanding and a significant tourist attraction. The implications for the government and stakeholders are in the development of tourism and cultural preservation policies, as well as the need for infrastructure investment, educational programmes, active promotion and developing better strategies in the preservation and promotion of historical tourism.